Information aspects in the theory of approximation and recovery of operators - Korneichuk, N. P. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We present a brief review of new directions in the theory of approximation which are associated with the information approach to the problems of optimum recovery of mathematical objects on the basis of discrete information. Within the framework of this approach, we formulate three problems of recovery of operators and their values. In the case of integral operator, we obtain some estimates of the error.